Many-core computing : hardware and software - Al-Hashimi, Bashir; Merrett, Geoff V. (Professional applications of computing series ;, 2019)
Computing systems have a tremendous positive impact on everyday life, from the Internet to mobile devices. However, they are facing a once-in-a-generation technical challenge, as the relentless half-century increase in processor speed for improving performance has come to an end. As a result, computing systems have switched from a focus on performance-centric serial computation to energy-efficient parallel computation. This switch is driven by the higher energy efficiency of using multiple slower processor cores instead of a single high-speed one. As the number of parallel cores increases, we continue to transition from the traditional single and multicore computing to many-core computing. The ability of these systems to compute, communicate, and respond to the real-world will transform how we work, do business, shop, travel, and care for ourselves, continuing to transform our daily lives and shaping the next phase of a digital society for the twenty first century.